Well-being interventions in U.S. colleges: a scoping review from a positive higher education perspective - Zhao, Grace X.; Zhao, Maggie Y.; Bean, Caitlin R.; Robbins, Ashley S.; Mahrer, Nicole E. (Frontiers in Psychology, 2025)
In response to growing concerns about student mental health, this scoping review synthesizes 40 peer-reviewed empirical studies published between 2009 and 2024 on well-being interventions for undergraduate students in U.S. higher education, examined through the emerging lens of Positive Higher Education. Drawing from diverse methodologies and interventions—including mindfulness, cognitive-behavioral therapy, psychoeducation, and positive psychology strategies—the review examines how well-being is defined, implemented, and assessed across curricular and co-curricular contexts. While many interventions demonstrated positive outcomes, particularly in reducing stress and enhancing psychological well-being, the field remains limited by conceptual ambiguity, inconsistent theoretical frameworks, and insufficient attention to long-term institutionalization and sustainability. Most studies lacked a clearly articulated definition of well-being, and relatively few were embedded in academic curricula. This review underscores the need for a coordinated, theory-informed approach to integrating well-being as a core educational outcome, aligned with the values of liberal arts education. It concludes with a call to develop a Positive Higher Education Implementation Toolkit to guide institutions in embedding well-being into policy, pedagogy, and practice.